Banana Xanthomonas wilt: a review of the disease, management strategies and future research directions - Biruma, M.; Pillay, M.; Tripathi, L.; Blomme, Guy; Abele, S.; Mwangi, M.; Bandyopadhyay, Ranajit; Muchunguzi, P.; Kassim, S.; Nyine, M.; Turyagyenda, L.F.; Eden-Green, S. (2007)
Banana production in Eastern Africa is threatened by the presence of a new devastating bacterial disease caused by Xanthomonas vasicola pv. musacearum (formerly Xanthomonas campestris pv. musacearum). The disease has been identified in Uganda, Eastern Democratic Republic of Congo, Rwanda and Tanzania. Disease symptoms include wilting and yellowing of leaves, excretion of a yellowish bacterial ooze, premature ripening of the bunch, rotting of fruit and internal yellow discoloration of the vascular bundles. Plants are infected either by insects through the inflorescence or by soil-borne bacterial inoculum through the lower parts of the plant. Short- and long-distance transmission of the disease mainly occurs via contaminated tools and insects, though other organisms such as birds may also be involved. Although no banana cultivar with resistance to the disease has been identified as yet, it appears that certain cultivars have mechanisms to ‘escape’ the disease. Management and control of the disease involve methods that reduce the inoculum’s density and spread of the pathogen. Removal of the male bud (de-budding) has proven to be very effective in preventing the disease incidence since the male bud appears to be the primary infection site. The economic impact of banana Xanthomonas wilt is not fully understood but its impact on food security in the region is very significant. While germplasm screening for the disease is ongoing, efforts to genetically engineer resistance in some banana cultivars are also making good progress. This paper presents a review of the disease and management strategies that have been successful in curtailing its spread.